2021
DOI: 10.3390/cancers13112564
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Characterization of Tumor Immune Microenvironment (TIME) in Malignant Pleural Mesothelioma

Abstract: Malignant pleural mesothelioma (MPM) is a rare and highly aggressive disease that arises from pleural mesothelial cells, characterized by a median survival of approximately 13–15 months after diagnosis. The primary cause of this disease is asbestos exposure and the main issues associated with it are late diagnosis and lack of effective therapies. Asbestos-induced cellular damage is associated with the generation of an inflammatory microenvironment that influences and supports tumor growth, possibly in associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 132 publications
(159 reference statements)
0
12
0
Order By: Relevance
“…Different studies have investigated the content of MPM tumoral stroma, as a source of prognostic markers and potential therapeutic targets. In mesothelioma, as with other tumor types, the stromal component plays an important role to support tumor growth and invasion [ 60 ] ( Figure 2 ). Lievense et al identified high expression of pro-inflammatory soluble cytokines in pleural effusion of MPM patients as well as in MPM cell line supernatant.…”
Section: Mesothelioma Microenvironment Crosstalk: Molecular Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have investigated the content of MPM tumoral stroma, as a source of prognostic markers and potential therapeutic targets. In mesothelioma, as with other tumor types, the stromal component plays an important role to support tumor growth and invasion [ 60 ] ( Figure 2 ). Lievense et al identified high expression of pro-inflammatory soluble cytokines in pleural effusion of MPM patients as well as in MPM cell line supernatant.…”
Section: Mesothelioma Microenvironment Crosstalk: Molecular Mechanismsmentioning
confidence: 99%
“…Additionally, a lower infiltration of immune cells has been correlated with high expression of stromal-related and connective-related genes in mesothelioma tissues [ 33 ]. MM contains a heterogenous population of immune cells, changing among patients and histological subtypes [ 32 , 60 ]. Because of the prognostic and therapeutical role of immune cells, the investigation of this area has recently attracted the interest of immune oncology research.…”
Section: Mesothelioma Microenvironment Crosstalk: Molecular Mechanismsmentioning
confidence: 99%
“…Every tumor (and, thus, MPM) is made with malignant cells plus stroma: the main and specific issue is related to the role played by asbestos (rather than activation of specific oncogenes) in both driving malignant transformation and modulating tumors surrounding stroma [2,12]. Although a deep description of MPM surrounding stroma goes beyond the scope of this review and can be available in detail in recently published literature, e.g., [2,[12][13][14][15], it is relevant to underline that the chronic inflammatory response to asbestos leads to the generation of a specific and heterogeneous stroma which sustains malignant transformation [16]. In detail, it determines an increased production of reactive oxygen species (ROS) and free radicals which recall inflammatory cells [17,18].…”
Section: Biologic Frame and Rationalementioning
confidence: 99%
“…In recent years, immune checkpoint inhibitors (ICIs) have shown remarkable results in treating multiple types of neoplasms. The etiology and pathogenesis of MPM are mostly attributed to the generation of an immune microenvironment favorable to tumor growth, caused by asbestos-induced damage [11]. There is evidence that ICIs might play an important role in the treatment of MPM; in fact, some encouraging results have emerged in recent years.…”
Section: Introductionmentioning
confidence: 99%